2005
DOI: 10.1093/rheumatology/kei115
|View full text |Cite
|
Sign up to set email alerts
|

Serum free prolactin concentrations in patients with systemic lupus erythematosus are associated with lupus activity

Abstract: An increase in serum free PRL levels, higher percentages of little PRL and lower percentages of big big PRL proved to be factors related to lupus activity in a subset of patients with SLE. These novel data must be taken into account in future studies aiming to establish a relationship between PRL and disease activity in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…To our knowledge, lupus is the only autoimmune disease where serum PRL levels have been measured discriminating the different isoforms of PRL [65]. This kind of analysis has outlined that levels of serum monomeric PRL (23 kDa) are higher in patients with active disease than in patients with nonactive disease, while there is a negative correlation between disease activity index and the percentage of the so-called "big big PRL" (>100 kDa), which is believed to have less biologic activity [65]. A recent study also identified a positive correlation between high PRL levels and disease damage in SLE [66].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…To our knowledge, lupus is the only autoimmune disease where serum PRL levels have been measured discriminating the different isoforms of PRL [65]. This kind of analysis has outlined that levels of serum monomeric PRL (23 kDa) are higher in patients with active disease than in patients with nonactive disease, while there is a negative correlation between disease activity index and the percentage of the so-called "big big PRL" (>100 kDa), which is believed to have less biologic activity [65]. A recent study also identified a positive correlation between high PRL levels and disease damage in SLE [66].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Prolactin may act as a cytokine and recent data show that PRL can break an autoreactive B-cells apoptosis and cause SLE in susceptible animals [25,26]. In humans, elevated serum PRL levels have been associated with active SLE [27] and immune cells from SLE patients produce more PRL than those from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, PRL levels have shown direct correlation with clinical and serological disease activity (16,(67)(68)(69). Results from several trials report also an association with neurological, renal and hematological involvement, serositis, enhanced anti-double-stranded DNA antibodies, and diminished complement (70,71). Furthermore, PRL bolsters the development of lupus-like phenotype in non-prone mice and exacerbated the disease in a lupus murine experimental study (72).…”
Section: Prl and Systemic Lupus Erythematosusmentioning
confidence: 99%